2007
DOI: 10.1093/annonc/mdm349
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant fatigue in cancer outpatients: the Edinburgh Cancer Centre symptom study

Abstract: CRF is common in cancer outpatients and is associated with type of disease and treatment, as well as with emotional distress. The association between CRF and emotional distress is strong but they are not equivalent conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…The existing fatigue data have been predominantly derived from breast cancer patients during their adjuvant treatment with radiation and/or chemotherapy, with some studies evaluating other patient cohorts after therapy or during treatment or groups of advanced cancer patients referred for specialized care 6 . Although these data focus on the construct of patient-reported fatigue rather than cancer-related fatigue, our findings are consistent with data related to cancer-related fatigue from other researchers who have found that approximately 30%–60% of patients have mild to moderate fatigue, approximately 20% of patients have severe levels of fatigue during or shortly after treatment for cancer, and approximately 10%–15% have fatigue as a chronic effect of treatment 2631 .…”
Section: Discussionsupporting
confidence: 91%
“…The existing fatigue data have been predominantly derived from breast cancer patients during their adjuvant treatment with radiation and/or chemotherapy, with some studies evaluating other patient cohorts after therapy or during treatment or groups of advanced cancer patients referred for specialized care 6 . Although these data focus on the construct of patient-reported fatigue rather than cancer-related fatigue, our findings are consistent with data related to cancer-related fatigue from other researchers who have found that approximately 30%–60% of patients have mild to moderate fatigue, approximately 20% of patients have severe levels of fatigue during or shortly after treatment for cancer, and approximately 10%–15% have fatigue as a chronic effect of treatment 2631 .…”
Section: Discussionsupporting
confidence: 91%
“…When fatigue prevalence (26.8%) and intensity (mean=5.8; SD=1.3; median=5.4) in this research were compared to studies involving other cancer patients, it was noted that fatigue was less frequent than in studies on patients in palliative care and receiving adjuvant chemotherapy or radiotherapy (1)(2) , and higher than some cancer survivors' experience, who reported 26% (8) . A slightly higher prevalence of fatigue (33%), using the same cut-off score as this study, was observed among colorrectal cancer patients in the United Kingdom (22) . This higher prevalence might be due to the instrument used for fatigue assessment.…”
supporting
confidence: 64%
“…However fatigue and depression should be regarded as separate entities. 43 There are some important negative fi ndings in this study. There were no signifi cant differences in any of the routine laboratory tests.…”
Section: Discussionmentioning
confidence: 74%